Producing writers using ICT facilities - Mat Daud, Nuraihan (2009)
In a typical language classroom, teachers tend to focus on form rather than function. The classroom environment is often unnatural and restricted to enable learners to put the language to authentic use. The question then is how to provide an environment that is supportive of developmental learning for emergent users of the language. This paper discusses a possible collaboration between teachers and parents to produce competent writers. It is based on a longitudinal study on a child who was given technological support to develop her writing skills. Several technological devices were used in this study. This included power-point software, wiki and skype facilities. It was found that a supportive environment encourages a child to apply her oral language to her production of written language. The study also shows that different types of language were produced when different technological devices were utilized.